Impacts of LED spectral quality on leafy vegetables: Productivity closely linked to photosynthetic performance or associated with leaf traits? - He, Jie; Qin, Lin; Chow, Wah Soon (International Journal of Agricultural and Biological Engineering, 2019)
The success of growing vegetables indoors requires the most appropriate selection of lighting spectrum. This mini review discusses the impacts of LED spectral quality on different leafy vegetables with a focus on the studies of Chinese broccoli (Brassica alboglabra), ice plants (Mesembryanthem crystallinum) and lettuce (Lactuca sativa L. cv. Canasta). For each species, plants exposed to different spectral LED lights were all under the same light intensity and same photoperiod. Chinese broccoli grown under red(R):blue(B)-LED ratio of 84:16 (16B) had the highest light-saturated photosynthetic CO2 assimilation rate (Asat) and stomatal conductance (gs sat) compared to plants grown under other R:B-LED ratios. It was also shown that 16B is the most appropriate selection for Chinese broccoli to achieve the highest shoot productivity with a rapid leaf number and leaf area development. The highest concentrations of photosynthetic pigments, soluble and Rubisco protein on a leaf area basis were also observed in 16B plants. The results conclusively affirmed that the highest productivity of Chinese broccoli grown under 16B is closely linked to the highest photosynthetic performance on a leaf area basis. For ice plants grown under R:B-LED ratios of 90:10 (10B), they had the highest shoot biomass with a faster leaf development compared to plants grown under other RB-LED combinations. However, there were no differences in Asat, gs sat, photosynthetic pigments, soluble and Rubisco proteins on a leaf area basis. In the case of lettuce plants, it was a surprise to observe that plants grown under 0B and 20G (20% green (G)-LED and 80% R-LED) had the highest shoot biomass, and largest total leaf area and light interception area but the lowest net maximal photosynthetic rate on a leaf area basis, compared to other plants. The combined RB-LED enhanced other photosynthetic parameters while 0B and 20G conditions had inhibitory effects on maximum quantum efficiency of PS II with lower photosynthetic pigments, total soluble protein and Rubisco protein. These results suggest that impacts of LED light quality on productivity of lettuce (L. sativa L. cv. Canasta) is closely linked to leaf traits not associated with photosynthetic performance on a leaf area basis.Keywords: leafy vegetable, leaf traits, LED spectral quality, photosynthetic performance, productivityDOI: 10.25165/j.ijabe.20191206.5178Citation: He J, Qin L, Chow W S. Impacts of LED spectral quality on leafy vegetables: Productivity closely linked to photosynthetic performance or associated with leaf traits? Int J Agric & Biol Eng, 2019; 12(6): 16–25.